RESOLUTION OF CONFLICTS IN THE FIELD OF HEALTH INSURANCE THROUGH MEDIATION - Мачуська, Ірина; Тітова, Олена; Чирик, Олена (SWorldJournal, 2025)
The article examines the institution of mediation as an alternative form of conflict resolution in the field of health insurance in Ukraine. It is noted that one of the priority areas of development of the medical sector is the development of health insur